Diversity and characteristics of culturable endophytic bacteria from Passiflora edulis seeds. Issue 4 (15th August 2021) - Ishida, Aoi; Furuya, Toshiki
Abstract: Defense compounds generally inhibit microbial colonization of plants. In this study, we examined the presence of endophytes in Passiflora edulis seeds that accumulate resveratrol and piceatannol at extremely high levels as defense compounds. Interestingly, although no microbial colonies appeared on an agar growth medium from the cut or homogenized seeds, colonies were generated from cut seedlings derived from the seeds. A total of 19 bacterial strains were isolated, of which 15 were classified as Gram‐positive. As we hypothesized that extremely high levels of piceatannol in the seeds would inhibit the growth of endophytes cultured directly from the seeds, we examined the antimicrobial activity of this compound against the isolated bacteria. Piceatannol exerted bacteriostatic rather than bactericidal effects on most of the bacteria tested. These results suggest that the bacteria remain static in the seeds due to the presence of piceatannol and are transmitted to the seedlings during the germination process, enabling colonies to be established from the seedlings on the agar medium. We also investigated the biocatalytic activity of the isolated bacteria toward resveratrol and piceatannol. One bacterium, Brevibacterium sp. PE28‐2, converted resveratrol and piceatannol to their respective derivatives. This strain is the first endophyte shown to exhibit such activity. Abstract : Bacterial endophytes were isolated from Passiflora edulis seeds that accumulate defense compounds at extremely high levels. Although no microbial colonies appeared on the agar growth medium from the cut or homogenized seeds, colonies were generated from cut seedlings derived from the seeds. The defense compound piceatannol exerted bacteriostatic rather than bactericidal effects on most of the isolated bacteria.